2007
DOI: 10.3171/foc.2007.22.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular events of brain metastasis

Abstract: ✓The brain is a privileged site of systemic cancer metastasis. The stages of the metastatic journey from the periphery to the brain are driven by molecular events that tie the original site of disease to the distant host tissue. This preference is not arbitrary but rather a directed phenomenon that includes such critical steps as angiogenesis and the preparation of the premetastatic niche. It appears that the connection between naïve brain and cancer cells is made in advance of any metastatic breach of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…MDA-MB-435 cells are aggressively metastatic breast cancer cells that share some characteristics with melanoma, 32,33 another tumor type that frequently causes brain metastasis in patients. 1 The MDA-MB-231/brain cell line was derived from MDA-MB-231 parental breast cancer cells after cardiac injection into immunodeficient mice and six cycles of isolating brain metastases and reinjection into the heart. 28 Here, we demonstrated that MDA-MB-231/brain cells, as well as MDA-MB-435 and 4T1 cancer cells, are suitable models for studying cancer cell interaction with the brain microvasculature even at the earliest time points, for following the ability of cancer cells to survive and grow within the brain tissue, and for analyzing involved host cell responses.…”
Section: Models and Kinetics Of Initial Cancer Cell Colonization Of Tmentioning
confidence: 99%
See 1 more Smart Citation
“…MDA-MB-435 cells are aggressively metastatic breast cancer cells that share some characteristics with melanoma, 32,33 another tumor type that frequently causes brain metastasis in patients. 1 The MDA-MB-231/brain cell line was derived from MDA-MB-231 parental breast cancer cells after cardiac injection into immunodeficient mice and six cycles of isolating brain metastases and reinjection into the heart. 28 Here, we demonstrated that MDA-MB-231/brain cells, as well as MDA-MB-435 and 4T1 cancer cells, are suitable models for studying cancer cell interaction with the brain microvasculature even at the earliest time points, for following the ability of cancer cells to survive and grow within the brain tissue, and for analyzing involved host cell responses.…”
Section: Models and Kinetics Of Initial Cancer Cell Colonization Of Tmentioning
confidence: 99%
“…1,2 Unfortunately, brain metastases are still very difficult to treat and the mechanisms underlying their establishment and progression are poorly understood. Thus, information in this direction and models for analysis are a prerequisite for the development of new, efficient therapies.…”
mentioning
confidence: 99%
“…Some authors support that the arrival of bone marrow-derived hematopoietic progenitors cells in distant sites represent early changes in the local environment (premetastatic niche) that dictates the pattern of metastatic spread and explains tumor dormancy (Kaplan et al 2005(Kaplan et al ,2006. Santarelli et al 2007, outline that the reactive monocytosis and activated microglia present in the premetastatic niche increase the local inflammatory response and can induce the growth of tumor cells transplanted to the brain. Furthermore these authors outline that it is plausible that the brain is able to generate the adequate environment in anticipation and preparation of the ensuing metastatic colonization (Santarelli et al 2007).…”
Section: Brain Metastases Biologymentioning
confidence: 99%
“…The potential of angiogenesis in breast metastases has been further been studied. VEGF has been reported to increase the penetration of metastatic MDA-MB-231 breast carcinoma and to play a role in brain metastases dormancy in the absence of inhibitory antiangiogenic factors (Kim et al 2004, Santarelli et al 2007, Palmieri et al 2007, Yano et al,. 2000, Kaplan et al 2005, Chen et al 2007).…”
Section: Brain Metastases Biologymentioning
confidence: 99%
See 1 more Smart Citation